Deceptive Communication - Despoina Alempaki; Valeria Burdea; Daniel Read (Center for Economic Studies and ifo Institute (CESifo), 2021)
In cases of conflict of interest, people can lie directly about payoff relevant private information, or they can evade the truth without lying directly. We analyse this situation theoretically and test the key predictions in an experimental sender-receiver setting. We find senders prefer to deceive through evasion rather than direct lying. This is because they do nοt want to deceive others, and they do nοt want to be seen as deceptive. The specific language of evasion does not matter. The results suggest deception should be tested in more naturalistic contexts with richer language.
Keywords: C91; D82; D83; D91; 330